Desempenho silvicultural e seleção de clones de Eucalyptus spp. para a qualidade da madeira - Beltrame, Rafael (2012)
The study aimed to evaluate the silvicultural performance of Eucalyptus spp. clones and select superior clones with higher quality of the wood. The material used for the study was from a clonal test of interspecific hybrids of Eucalyptus spp., in the municipality of Tapes - state of Rio Grande do Sul, belonging to company CMPC Celulose Riograndense. The forest stand was established in August 2003, with initial spacing of 3.0 x 3.0 m, containing 138 clones. The clones were grouped by the diameter at breast height (DBH) and overall height (h), and 29 of them were selected for the study. For the sampling of trees DBH, h, bark thickness (EC), dynamic modulus of elasticity (Ed) using ultrasound and longitudinal residual strain (DRL) resulting from growth stresses. The DRL was measured in living trees with the extensometer method CIRAD-Fôret. Afterwards, 58 trees were felled and broken into logs to evaluate end splitting planks were taken to prepare speciments for wood physical and mechanical properties according to D 143-94 - ASTM (2000) standards. The end logs splitting (IRT) was evaluated in the field, covering the logs end during five days for subsequent measurement. The phenotypic variance components and indirect gain selection estimate for the clones in this study were determined by DRL, wood volume (Vsc), basic density (ρpond) and IRT. The clones showed enough genetic variability to be separated into groups according to DHB at three and seven years, and for h at seven years of age. The early selection at three years after planting can be used to identify Eucalyptus spp. clones with best growth. The DRL showed variability among clones, but no correlation with the dendrometric variables. The mean value for IRT was 0.46%. The DRL was highly correlated with TCL and IRT, however the ρpond and mechanical properties showed no correlations with the DRL. The clones belonging to group 1, which present the lowest levels for TCL and consequently lower IRT, can be considered potential for forest breeding programs. Clone selection performed by the variable DRL, Vsc, ρpond and IRT, provided satisfactory genetic gains, by improving the growth characteristics or improving quality of the wood.